A new kind of vertically aligned field emission transistor with a cylindrical vacuum channel. (March 2017) - Shen, Zhihua; Wang, Xiao; Wu, Shengli; Tian, Jinshou
Abstract: This study investigated a vertically aligned field emission transistor with a cylindrical vacuum channel. The channel length of this proposed transistor can be precisely controlled and easily fabricated to be comparable to the mean free path of electrons in air so that the device can operate in the air without performance degradation. In the study, this vacuum transistor showed a low threshold voltage (1.2 V, 2.2 V, and 3.3 V) with a gate dielectric thickness of 10 nm, 15 nm, and 20 nm and a subthreshold slope of 1.1 V/dec. It was found that the vacuum channel radius should be no less than 20 nm, otherwise, severe performance degradation will appear due to the effect of the gate shield (leading to reduction of the anode current) and electron collision events with the dielectric layer (presenting reliability issues). This kind of vacuum transistor may have wide applications in extreme conditions such as high temperature and intense irradiation. Highlights: The proposed vacuum transistor can operate in air due to the nano-sized channel length. A wider channel radius may help improve the performance of the device (more reliable and higher current). This work may help understand the working principle and benefit the advanced design of such device.